Determining Factors for the Success of Halal Certification in Sidrap Regency - Bahtiar Herman; Inna Mutmainna Cahyani Thahir; Erwin Irnandi; Fakhrul Indra Hermansyah; Ihya' Ulumuddin; Naufal Muhammad Aksah (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2025)
This study aims to examine the influence of halal information, promotion, and brand image on consumer purchase intention toward halal products, with perceived value as a moderating variable. Employing a quantitative research design with a sample of 377 respondents in Indonesia, data were collected using a structured questionnaire and analyzed through Structural Equation Modeling (SEM-PLS). The findings demonstrate that halal information, promotional efforts, and brand image significantly influence consumer purchase intentions. Furthermore, perceived value strengthens the relationships between these factors and consumer trust, ultimately impacting purchase decisions. The originality of this study lies in its comprehensive integration of key variables—halal information, promotion, brand image, and perceived value—into a unified model that enhances understanding of consumer behavior in the halal market. From a practical perspective, this study highlights the strategic importance for halal product marketers to deliver transparent halal information, adopt value-driven promotional strategies, and build a trustworthy brand image to appeal to increasingly discerning consumers. Socially, the study contributes to promoting ethical consumption aligned with Islamic values. While the results are promising, future research could expand the geographical scope or include comparative analysis across different demographic segments to generalize findings further.